The THE EFFECT OF UTILIZING ASIAN CLAM (Anodonta woodiana) AS A SUSPENSION FEEDER ON THE WATER QUALITY OF NILE TILAPIA (Oreochromis niloticus) IN A YUMINA BUMINA SYSTEM WITH MINIMAL LAND USE - Alexander Burhani Marda; Risca Permatasari; Dita Haryanti; Arya Yuda Saputra (Jurnal Perikanan Unram, 2024)
Integrated Multi-Trophic Aquaculture (IMTA) has limitations in its application due to the requirement for large cultivation areas. To address this issue, the IMTA system has been modified into the yumina bumina system, utilizing freshwater mussels (Anodonta woodiana) as suspension feeders and water spinach (Ipomoea reptans) as nitrogen absorbers. This study employed a completely randomized design with three treatments: (A) Nile tilapia without freshwater mussels, (B) Nile tilapia with 25 freshwater mussels per 15L, and (C) Nile tilapia with 50 freshwater mussels per 15L, over a 30-day period. The results indicated that the addition of freshwater mussels increased nitrite and nitrate levels in treatments B and C, yet supported specific growth rates of Nile tilapia in terms of length and weight, with the highest values observed in treatment C (1.05%/day) and B (3.75%/day), respectively. The system also achieved a survival rate of Nile tilapia above 80% with acceptable water quality parameters, including neutral pH (7.86–8.16) and high dissolved oxygen levels (17.77–18.02 mg/L). This integration demonstrates significant potential for optimizing Nile tilapia production efficiently while ensuring environmental sustainability.